ASUHAN KEPERAWATAN PADA Nn. A DENGAN POST OP FIBROADENOMA MAMMAE DI RUANG KHODIJAH RSUD BANGKINANG - Resti Agestia; Ridha Hidayat (Jurnal Spektrum Kesehatan Indonesia, 2026)
Fibroadenoma mammae is a benign breast tumor commonly affecting women of reproductive age, characterized by a firm, movable lump. This study aims to apply nursing care for a post-operative fibroadenoma mammae patient, covering assessment, diagnosis, planning, implementation, and evaluation. The method used was a descriptive case study with data collection through interviews, observation, physical examination, supporting examinations, and documentation. The subject was Mrs. A, 17 years old, diagnosed with fibroadenoma mammae, studied from June 1–3, 2026. During assessment, the patient reported pain at the right breast surgical wound, increasing with movement, sharp in quality, and intermittent. The researchers formulated the primary nursing diagnoses: acute pain related to a physical injuring agent (surgical procedure) and disturbed sleep pattern related to physical restraint. The intervention implemented focused on nonpharmacological techniques, namely deep-breathing relaxation to reduce pain. Nursing care was carried out according to the care plan and produced results, with the patient’s problems resolved during three days of visits. This report is expected to serve as a reference for nursing care of post-op fibroadenoma mammae.